2002
DOI: 10.1002/app.10558
|View full text |Cite
|
Sign up to set email alerts
|

Studies on graft copolymerization of 4‐vinylpyridine onto guar gum

Abstract: Graft copolymerization of 4-vinylpyridine (4-VP) onto guar gum (GOH) using potassium monopersulfate (PMS)/thioacetamide (TAA) as a redox pair was studied in an aqueous medium under inert atmosphere. The concentration of potassium monopersulfate and thioacetamide should be 1.0 ϫ 10 Ϫ2 and 5.0 ϫ 10 Ϫ3 mol dm Ϫ3 , respectively, for highest grafting ratio and efficiency. Efficient grafting was observed at 19.25 ϫ 10 Ϫ2 and 4.87 ϫ 10 Ϫ2 mol dm Ϫ3 concentration of 4-vinylpyridine and sulfuric acid, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…5), the following additional bands were appeared in the spectra of xanthan-gum-g-(4-vinyl pyridine). Following observation was also observed in previous publication 31 • Poly (4-vinyl pyridine) ring stretching vibration occurred in the region at 1505.8 cm À1 and 1454.1 cm…”
supporting
confidence: 79%
“…5), the following additional bands were appeared in the spectra of xanthan-gum-g-(4-vinyl pyridine). Following observation was also observed in previous publication 31 • Poly (4-vinyl pyridine) ring stretching vibration occurred in the region at 1505.8 cm À1 and 1454.1 cm…”
supporting
confidence: 79%
“…1,19,26 On the other hand, 4-VP had a high affinity for its homopolymer substrate, which meant that the homopolymerization occurred in the polymer phase to a large extent. Thus, it is likely that homopolymerization had more chances to occur, and as a result, a decrease in G% and E% was observed.…”
Section: -Vp/kgm Graft Copolymerizationmentioning
confidence: 98%
“…27 Consequently, we concluded that the grafting of 4-VP onto KGM took place at the site of the hydroxyl groups onto the KGM backbone. 19 …”
mentioning
confidence: 97%
“…It should be recognized that although glutaraldehyde is toxic, its toxicity could be reduced significantly after its crosslinking. [11][12][13][14][15][16][17][18][19][20][21] In this investigation, we set out to examine preparation and property of crosslinking GG in order to improve the poor performance of the GG.…”
Section: Introductionmentioning
confidence: 99%